Assessment of creativity evaluation skills: A psychometric investigation in prospective teachers. (September 2016) - Benedek, Mathias; Nordtvedt, Nora; Jauk, Emanuel; Koschmieder, Corinna; Pretsch, Jürgen; Krammer, Georg; Neubauer, Aljoscha C.
Highlights: A new test of creativity evaluation skills is presented. More creative people evaluate the creativity of others' ideas more accurately. People tend to underestimate the creativity of ideas. Openness, intelligence and language competence predict lower underestimation. Abstract: An accurate judgement of the creativity of ideas is seen as an important component underlying creative performance, and also seems relevant to effectively support the creativity of others. In this article we describe the development of a novel test for the assessment of creativity evaluation skills, which was designed to be part of an admission test for teacher education. The final test presents 72 ideas that have to be judged as being common, inappropriate, or creative. Two studies examined the psychometric quality of the test, and explored relationships of creativity evaluation skills with cognitive ability and personality. In the first study, we observed that creativity evaluation skills are positively correlated with divergent thinking creativity and creative achievement, which suggests that evaluation skills are relevant for creative ideation as well as creative accomplishment. Across both studies, people tended to underestimate the creativity of ideas. Openness, intelligence and language competence predicted higher creativity evaluation skills, and this effect was partly mediated by a less negative evaluation bias. These findings contribute to our understanding of why people sometimes fail to recognize the creativity in others.